Profesinių technikos mokyklų moksleivių skaitymo tyrimai - Mockienė, Birutė (Knygotyra, 1986)
In the last twenty years the reading of schoolchildren of VTS has been investigated less than the reading of the other young people. The analysis of published works on this question has shown that the general problems of reading were investigated more than special questions. Some data about the content of reading, literature apprehension have been obtained.Investigations have been undertaken with different aims and methods and in consequence the results are far from comparable to each other and even contradictory.The investigations draw a conclusion that the schoolchildren of VTS must be reputed as a specific group of readers. The allot time for reading, the content of reading, the literature apprehension of these young were determinated by the tasks of their socialization period. The empirical investigations came to conclusions about the necessity to draw more attention to the questions of formation of the reading interests among schoolchildren, to study the work of the libraries of VTS, to coordinate the work of libraries where the schoolchildren of VTS.